2016
DOI: 10.1371/journal.pone.0152104
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of PI3K/AKT and MAPK Signaling Pathways in Melanoma Cancer

Abstract: BackgroundMalignant melanoma is an aggressive tumor of the skin and seems to be resistant to current therapeutic approaches. Melanocytic transformation is thought to occur by sequential accumulation of genetic and molecular alterations able to activate the Ras/Raf/MEK/ERK (MAPK) and/or the PI3K/AKT (AKT) signalling pathways. Specifically, mutations of B-RAF activate MAPK pathway resulting in cell cycle progression and apoptosis prevention. According to these findings, MAPK and AKT pathways may represent promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…This experiment confirmed that AKT phosphorylation promoted the phosphorylation of ERK1/2 and NF-κB and that the PI3K/AKT pathway positively regulated ERK1/2 and NF-κB signaling pathways. Our results also confirmed that ERK1/2 signaling negatively regulated the PI3K/AKT signaling pathway and positively regulated NF-κB signaling, consistent with previously reported experimental results [34,[48][49][50][51][52]. In this study, the pharmacodynamic analyses were consistent with the results of q-PCR and Western blot, which showed that Kaji-ichigoside F1 and Rosamultin could inhibit mitochondrial apoptosis by altering the expression of mitochondrial apoptosis-related genes, including Bcl-2, Bax, Cyt C, caspase 9, and caspase 3.…”
supporting
confidence: 92%
“…This experiment confirmed that AKT phosphorylation promoted the phosphorylation of ERK1/2 and NF-κB and that the PI3K/AKT pathway positively regulated ERK1/2 and NF-κB signaling pathways. Our results also confirmed that ERK1/2 signaling negatively regulated the PI3K/AKT signaling pathway and positively regulated NF-κB signaling, consistent with previously reported experimental results [34,[48][49][50][51][52]. In this study, the pharmacodynamic analyses were consistent with the results of q-PCR and Western blot, which showed that Kaji-ichigoside F1 and Rosamultin could inhibit mitochondrial apoptosis by altering the expression of mitochondrial apoptosis-related genes, including Bcl-2, Bax, Cyt C, caspase 9, and caspase 3.…”
supporting
confidence: 92%
“…Another strategy of cancer cells used to inhibit the efficacy of treatment is enhanced expression of pathways involved in cancer proliferation and survival. With regard to melanoma RAS-RAF-MEK-ERK (MAPK, mitogenactivated protein kinase) and PI3K-AKT signalling pathways can be differentiated, which in addition can interact with each other [64,65]. They are activated, among others, by NRAS, BRAF mutations as well as by loss of PTEN properties (PI3K kinase phosphatase) and stimulation of growth factors including VEGF.…”
Section: Survival and Proliferation Pathwaysmentioning
confidence: 99%
“…63,64 The widely observed mechanisms are mutation of neuroblastoma-RAS (NRAS mutations-NRAS Q61 ; NRAS T58 ; NRAS G13R ), 65 loss of neurofibromatosis type-1(NF1), 66-68 loss of phosphatase and tensin homolog (PTEN), 69,70 up-regulation of cancer Osaka thyroid kinase (COT), 71 mutation of MEK, 63,69 negative feedback inactivation of extracellular-related kinase (ERK) and alteration in phosphoinositide 3-kinase-AKT (PI3K-AKT) pathway. 64,72 …”
Section: P53mentioning
confidence: 99%